Use of Spark Plasma Sintering for Fabrication of Porous Titanium Aluminide Alloys from Elemental Powders. Issue 6 (25th April 2016) - Du, H.; Liu, X. W.; Li, J.; Tao, P.; Jiang, J.; Sun, R.; Fan, Z. T.
Abstract : Porous titanium aluminide alloys were fabricated by spark plasma sintering (SPS) plus postheat treatment from titanium and aluminum elemental powders using sodium chloride as the space holders. Various interconnected porosities were achieved by SPS at 600°C/10 MPa, followed by water dissolution to remove sodium chloride. The phase transformation between titanium and aluminum, however, was not accomplished. Two kinds of postheat treatment, pressureless SPS and vacuum annealing, were employed to obtain the phase transformation. Results showed that most of the pores formed before were retained and the phase transformation, formation of γ and α2 phases, were completed during vacuum annealing. Whereas a great deal of pores were disappeared after pressureless SPS.